Morphological Identification of Bolbosoma turbinella (Acanthocephala) in Sei Whale (Balaenoptera borealis) from Straits of Malacca, Malaysia - Mohd Ihwan Zakariah; Mohd Tamimi Ali Ahmad; Mohd Shafiq Razak; Norainy Mohd Husin; Wahidah Wahab; Rabi-Atun Adawiah Abdullah; Nor Asma Husna Yusoff; Surzanne Agos; Marina Hassan (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • Identification of Morphological characteristic of the Bolbosoma sp. • Genetic confirmation of the specific species of Bolbosoma turbinella. • The first report in Straits of Malacca. • Health status of Sei Whale (Balaenoptera borealis).